Rancang Bangun Handle Forklift Berbasis Sistem Aktuator Linear Electrical Kapasitas 40kg - Burhanuddin; Miner; Alif Darmawan B.; Andi Sulaeman (Program Pendidikan Vokasi Teknik Mesin, 2023)
A forklift is a type of truck that is operated to lift, move, and unload goods from one place to another. Forklift operation can be done indoors or outdoors. With the forklift can increase effectiveness and efficiency in operational activities. The use of forklifts can also ease the burden on employees, especially in terms of moving goods. The purpose of this final project is to design and manufacture a forklift with a 40 kg linear electrical actuator system. The initial process of lifting is to connect the cable from the switch to the accu then push the forklift handle tool towards the object or media to be lifted then, push the switch lever up according to the desired height, (Please note the maximum lifting height of this tool is 1700mm and the maximum load is 40 kg). After the object or media is lifted, push the tool to the seventh place, then lower the tool by pushing the switch lever down and then gently pull the forklift handle. The rest results show that this tool is able to lift loads for a long time with a maximum load weight of 40 kg and a maximum height of 1700 mm. The conclusion of making this final project is how to design and make forklift handles based on linear electrical actuators consisting of frames, actuators, dynamos with a power of 120 Volt and a battery current of 12 A. Applications used for the design of this tool are sketch-up. Equipment specifications working voltage 12 volts, maximum lifting height 1700mm, lifting load 40kg, operation using the ON OFF ON switch, and 12 volt Accu power source. To maximize the performance of this forklift tool can use a hydraulic system.